Development of Digital Media for Learning Arabic Al-Qur’an language for Blind Students - Rohman , Baeti; Jarudin; Khuzaimah, Prajka Ibnu (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to develop digital media for learning Arabic Al-Qur’an language for blind students. The research procedure has two steps, first, developing digital media learning and supplementary materials, second, testing developed media. Data were analyzed to calculate percentages, averages, standard deviations, and t-tests. The findings revealed that: the learning media developed consisted of four components, namely objectives, strategies, content structure, assessment instruments, learning material, and evaluation. Effectiveness test, with pretest and posttest with 0.05 statistically significant differences and so are normal studies. Based on the test results from the average difference between the pre-test and post-test values. The test results found that the value of t equal to -7,238 with sig. (2-tailed) 0,000. This shows that there is a difference between the pre-test value and the post-test value and because the t-value found is negative then this shows that the post-test value is better than the pre-test value, it can be concluded that digital media is effective for language learning Arabic Al-Qur’an in helping blind students. The results showed a significant increase in learning outcomes of 1.04 units based on a comparison of pretest and posttest meaning that the media developed were effective for use. This research implies that digital media is very effective in helping to learn for blind students.